Analisa Semiotika Kekerasan Pada Acara Musik Dahsyat dan Inbox di Televisi - Pratiwi, Setyo Budi (Universitas Semarang, 2015)
The proliferation of television stations, tightened competition to deliver a more attractive event, which aired treats contain many elements of violence and consequently a lot of television shows that negative impersonation. The purpose of this study is to prove that there is an element of violence in the show music show on television, as well as knowing the forms of symbolic violence contained in the event. The object of this study is event Strikes and Inbox. This study uses a semiotic analysis of Roland Bartes to show the meaning of denotation, connotation to the myth of the display to see the event. The results obtained are in the Inbox event Strikes and violence are both verbal and non-verbal in every episode. It is proved that the event is not eligible to be broadcast as it can lead to impersonation or imitation of Indonesian society. If there is no control from the government or agency concerned it will impact the loss of a sense of empathy and culture of politeness that characterizes the Indonesian nation.